2017
DOI: 10.18632/oncotarget.20991
|View full text |Cite
|
Sign up to set email alerts
|

Trends in neoadjuvant chemotherapy use and oncological outcomes for muscle-invasive bladder cancer in Japan: a multicenter study

Abstract: ObjectiveDespite benefits of neoadjuvant chemotherapy (NAC), the adoption of guideline recommendations for NAC use in patients with muscle-invasive bladder cancer (MIBC) has been slow. We aimed to evaluate temporal trends in NAC use and oncological outcomes in a representative cohort of patients with MIBC.MethodsWe included 532 patients from 4 hospitals who underwent radical cystectomy (RC) for ≥ cT2 MIBC in 1996–2017. We retrospectively evaluated temporal changes in NAC use and progression-free and overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
5
24
0
Order By: Relevance
“…This could be a result of small percentage of Asians in this cohort. In fact, a large study from Japan showed similar stage distribution to Caucasians in TCGA cohort and similar mean age at diagnosis to Caucasians in our study [23].…”
Section: Discussionsupporting
confidence: 86%
“…This could be a result of small percentage of Asians in this cohort. In fact, a large study from Japan showed similar stage distribution to Caucasians in TCGA cohort and similar mean age at diagnosis to Caucasians in our study [23].…”
Section: Discussionsupporting
confidence: 86%
“…Contrary to our data and that of the Koreans is the NAC utilization rate in Japan. A recent publication from Anan et al found 83% utilization rate over the past decade 17 . It should be noted however that 83% of their patient's cohort received carboplatin based NAC, a regimen not recommended in the United States 7 .…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…We selected three courses of neoadjuvant GCb and this patient obtained the pathological complete response. Although inferior efficacy of a carboplatin‐based regimen has been suggested, our previous study showed a low toxicity GCb regimen facilitated in completion of NAC, prevention of the delay in RC, and resulted in a favorable oncological and QOL outcome . Therefore, neoadjuvant GCb might be an alternative option for MIBC patients with renal implement.…”
Section: Discussionmentioning
confidence: 94%
“…MIBC patients with a history of pelvic irradiation have been reported with more advanced disease than de novo MIBC . Cisplatin‐based NAC improves survival outcomes in patients with MIBC . However, the efficacy of NAC for irradiation‐related MIBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%